Peran Resiliensi Sebagai Prediktor Terhadap Work Life Balance Pada Pekerja Di Masa Pandemi Covid-19 - Istiqamah, St Hadjar Nurul; Ismail, Ismalandari (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
This study aims to determine the role of resilience in workers' work life balance during the Covid-19 pandemic. Respondents amounted to 73 respondents who had an age range 25-40 years and have been married status. The instrument in this study used the Connor-Davidson Resilience Scale-10 with 10 question items and the work life balance from Fisher, Bulger and Smith with 16 question items. Sampling technique used is random sampling. The data analysis technique in this research uses simple regression analysis. The results obtained indicate that there is a positive contribution of resilience as a predictor to work life balance of 24.3% with a correlation coefficient of 0.493.